1994
DOI: 10.1007/bf00021295
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an abandoned roast yard on the fish and macroinvertebrate communities of surrounding beaver ponds

Abstract: Recently formed beaver-ponds surrounding an abandoned copper-nickel ore roast yard near Sudbury, Ontario, Canada, were influenced by highly acidic and heavy-metal contaminated effluent . Fish, including Culaea inconstans, Phoxinus neogaeus, Phoxinus eos, and Pimephales promelas, were found in the ponds upstream of the roast yard only . Macroinvertebrate taxon richness and diversity were greater in the upstream ponds than in the downstream ponds . Acid intolerant taxa, including Mollusca and Hyalella azteca, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Group: 1, no AMD impact (n = 5); 2, intermittent AMD (n = 3); 3, acidic AMD (n = 4); 4, neutral AMD (n = 3); 5, higher order (n = 4). also responded to AMD impacts, as has been observed in other studies (e.g., Roback and Richardson 1969;Armitage 1980;Rutherford and Mellow 1994), increasing in relative abundance at the acidic AMD stations compared with unimpacted sites. These findings suggest that this watershed was a good system to use in a comparison of transplanted Asian clam responses to AMD with those of the resident community.…”
Section: Discussionsupporting
confidence: 78%
“…Group: 1, no AMD impact (n = 5); 2, intermittent AMD (n = 3); 3, acidic AMD (n = 4); 4, neutral AMD (n = 3); 5, higher order (n = 4). also responded to AMD impacts, as has been observed in other studies (e.g., Roback and Richardson 1969;Armitage 1980;Rutherford and Mellow 1994), increasing in relative abundance at the acidic AMD stations compared with unimpacted sites. These findings suggest that this watershed was a good system to use in a comparison of transplanted Asian clam responses to AMD with those of the resident community.…”
Section: Discussionsupporting
confidence: 78%
“…In 1995, the USEPA Office of Surface Mining reported that acid mine drainage, or AMD, was the single greatest threat to water quality in the Appalachian Mountain region of the USA. In addition, the effects of AMD on benthic macroinvertebrates have been extensively documented (Smith and Frey 1971;Herricks and Cairns 1974;Armitage 1980;Rutherford and Mellow 1994;Cherry et al 1995Cherry et al , 1997Cherry et al , 2001Winterbourn and McDiffet 1996) and have shown that biodiversity is generally reduced in streams impacted by AMD. Specifically, Clements (1991) found I. bicolor to be highly sensitive to heavy metals.…”
Section: Introductionmentioning
confidence: 97%
“…Rutherford and Mellow (1994) have documented similar effects in borderline circumneutral waters below AMD inputs. They observed decreased !axon richness and total abundance at two stations ( average pH values of 6.2 and 5.9) downstream of a pH 3.5 site.…”
Section: Discussionmentioning
confidence: 70%
“…Changes in plankton community structure include reductions in the number oftaxa present and/or shifts from intolerant to tolerant species. Similar (Armitage 1980;Herricks and Cairns 1974;Rutherford and Mellow 1994;Smith and Frey 1971;Soucek et al 2000a), and fish (Rutherford and Mellow 1994) exposed to AMD.…”
Section: Introductionmentioning
confidence: 92%